A Qualitative Inquiry into the Institutional Sustainability of Mental Health Programs in the Divine Word Colleges of the SVD Central Province - Solo III, Mark; Perez, Monaliza; Mendoza, Shirley; Carandang, Rommel (JPAIR Multidisciplinary Research, 2026)
The study explored the institutional sustainability of mental health programs at the Divine Word Colleges of the SVD Central Province. While many higher education institutions in the Philippines run mental health initiatives, there is limited evidence on how these programs are maintained over time, especially in faith-based colleges. This gap motivated the current research. It examined existing practices, support systems, and institutional factors that affect the long-term viability of mental health programs at the Divine Word Colleges in Calapan, Legazpi, and San Jose. The analysis was guided by national frameworks, including Republic Act 11036, Department Order No. 208, and the Philippine Council for Mental Health’s Strategic Framework 2024–2028. The study applied a qualitative research design. Data collection involved in-depth interviews and document review with administrators, faculty, and employees. Thematic analysis involved systematic reading, coding, categorization, and theme development to identify patterns related to program sustainability. Findings identified key institutional factors influencing sustainability. These factors include leadership support, policy integration, resource allocation, and stakeholder engagement. The study produced a context-based model to support the sustained implementation of mental health programs in faith-based higher education institutions. The results present practical guidance for strengthening institutional mental health systems and maintaining supportive academic environments across the Divine Word Colleges of the SVD Central Province.
Keywords: mental health program; sustainable intervention; qualitative design; institutional support; well-being; academic environment